Mechanisms of Desiccation Tolerance: Themes and Variations in Brine Shrimp, Roundworms, and Tardigrades - Hibshman, Jonathan D.; Clegg, James S.; Goldstein, Bob (Frontiers in Physiology, 2020)
Water is critical for the survival of most cells and organisms. Remarkably, a small number of multicellular animals are able to survive nearly complete drying. The phenomenon of anhydrobiosis, or life without water, has been of interest to researchers for over 300 years. In this review we discuss advances in our understanding of protectants and mechanisms of desiccation tolerance that have emerged from research in three anhydrobiotic invertebrates: brine shrimp (Artemia), roundworms (nematodes), and tardigrades (water bears). Discovery of molecular protectants that allow each of these three animals to survive drying diversifies our understanding of desiccation tolerance, and convergent themes suggest mechanisms that may offer a general model for engineering desiccation tolerance in other contexts.